Going Home : Black Representatives and Their Constituents. - Fenno, Richard F., 1926-2020 (University of Chicago Press, 2011)
Thirty years ago there were nine African Americans in the U.S. House of Representatives. Today there are four times that number. In Going Home, the dean of congressional studies, Richard F. Fenno, explores what representation has meant--and means today--to black voters and to the politicians they have elected to office. Fenno follows the careers of four black representatives--Louis Stokes, Barbara Jordan, Chaka Fattah, and Stephanie Tubbs Jones--from their home districts to the halls of the Capitol. He finds that while these politicians had different visions of how they should represent their distr.